Estilos de liderazgo del director según percepción docente y autoevaluación del desempeño docente en una institución de Ventanilla - Idone Cochachi, Teodora Máxima (2012)
The present investigation was to determine leadership styles as director and teacher perceptions of teacher performance self-assessment in an educational institution of Ventanilla. The investigation was conducted under the descriptive methodology. The sample is composed of 41 teachers, taken for study variables director leadership styles democratic, authoritarian, laissez faire and pedagogical skills, emotional, accountable performance of their job functions, relationships and results of educational work. For data collection a questionnaire was applied to other leadership styles and teacherperformance and validated. The reliability of the instrument of leadership styles coefficient obtained de.945 * Global Alpha, the teacher performance instrument obtained a Cronbach coefficient of 0.956. The results show that a (51.22%) of teachersare fairly in line with the democratic style and the responsibilities in the performance of his duties (41.4%) is in the middle. We conclude that the democratic leadership style director increases teacher participation in school activities.